2007
DOI: 10.1111/j.1365-2265.2007.02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of endogenous sex hormone with C‐reactive protein levels in middle‐aged and elderly men

Abstract: Endogenous total and bioavailable E2 levels are significantly associated with CRP among middle-aged and elder men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Just as observed here for AAG, such therapy produced non-significant increases in CRP (Aversa et al, 2010;Kapoor et al, 2007;Nakhai Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) and fibrinogen (English et al, 2000). Larger trials, or new information from completed trials, are needed to determine whether testosterone or dihyrotestosterone therapy has the positive relation with markers of systemic inflammation, as indicators of a less well-functioning immune system, which might be expected from a theoretical life history perspective.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Just as observed here for AAG, such therapy produced non-significant increases in CRP (Aversa et al, 2010;Kapoor et al, 2007;Nakhai Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) and fibrinogen (English et al, 2000). Larger trials, or new information from completed trials, are needed to determine whether testosterone or dihyrotestosterone therapy has the positive relation with markers of systemic inflammation, as indicators of a less well-functioning immune system, which might be expected from a theoretical life history perspective.…”
Section: Discussionsupporting
confidence: 71%
“…The available evidence from these RCTs generally shows little effect of testosterone therapy on CRP (Aversa et al, 2010;Frederiksen et al, 2013;Kapoor et al, 2007;Nakhai-Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) or fibrinogen (Smith et al, 2005), although one RCT reported testosterone decreased CRP (Kalinchenko et al, 2010) among a subset of men. Larger observational studies among men usually, but not always, report serum testosterone inversely associated with CRP (Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Nakhai Pour et al, 2007;Zhang et al, 2013), white blood cell counts and/or its differentials (Brand et al, 2012;Haring et al, 2012;Tang et al, 2007) and fibrinogen (Bonithon-Kopp et al, 1988;Haring et al, 2012;Yang et al, 1993). Experimental and observational evidence may differ for a number of reasons: the small size of most RCTs of testosterone therapy, differences in the action of exogenous and endogenous testosterone, serum testosterone acting as a marker of health status or serum testosterone not capturing all androgen activity (Labrie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The few existing studies investigating the association between sex hormone concentrations and inflammatory markers yielded inconsistent results and were limited by small study samples and cross‐sectional design, respectively. Although in some studies different sex hormones were not correlated with inflammatory biomarkers (Van Pottelbergh et al, 2003; Maggio et al, 2006; Nakhai Pour et al, 2007), other studies showed inverse correlations of TT, free T, and SHBG with hsCRP (Laaksonen et al, 2003; Kapoor et al, 2007; Laughlin et al, 2008; Kupelian et al, 2010), and positive correlations of DHEAS with hsCRP (Laaksonen et al, 2003). Therefore, our study confirms, at least in part, previous results in not finding an association between sex hormone concentrations in men and hsCRP (Van Pottelbergh et al, 2003; Maggio et al, 2006; Nakhai Pour et al, 2007) in cross‐sectional as well as longitudinal analyses.…”
Section: Discussionmentioning
confidence: 95%
“…But the association between sex hormone concentrations and inflammatory biomarkers remains inconclusive, because the few existing studies are based on cross‐sectional samples that provide no evidence of the direction of the effect or small‐scale clinical trials. Although some cross‐sectional studies found no correlation between sex hormones in men and inflammatory biomarkers including high‐sensitive C‐reactive protein (hsCRP; Van Pottelbergh et al, 2003; Maggio et al, 2006; Nakhai Pour et al, 2007), others observed inverse correlations of total testosterone (TT), free testosterone (free T), and sex hormone—binding globulin (SHBG) with hsCRP (Laaksonen et al, 2003; Kapoor et al, 2007; Laughlin et al, 2008; Kupelian et al, 2010).…”
mentioning
confidence: 99%
“…On the other hand, in male‐to‐female transsexuals who were treating with ethyniloestradiol 100 μg per day orally had had increased the risk of a venous thrombosis and/or pulmonary embolism 38 . Moreover, chronic inflammation has emerged as an important independent predictor of CAD, 39 and a positive correlation between E 2 and C‐reactive protein levels in middle‐aged and elderly men was described 40 . Furthermore, E 2 increases apoptosis in human coronary artery endothelial cells by up‐regulation of Fas and Fas‐ligand expression 41 .…”
Section: Discussionmentioning
confidence: 99%